1996
DOI: 10.1046/j.1365-2958.1996.5421065.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Penicillium chrysogenum gene encoding a PacC transcription factor and its binding sites in the divergent pcbAB–pcbC promoter of the penicillin biosynthetic cluster

Abstract: Previous work established that pH regulation of gene expression in Aspergillus nidulans, a major determinant of penicillin biosynthesis, is mediated by the zinc-finger transcription factor PacC, an activator of transcription of the isopenicillin N synthase gene. We characterize here the pacC gene from the efficient penicillin producer Penicillium chrysogenum, which functionally complements an A. nidulans pacC null mutation. It encodes a 641-residue polypeptide showing 64% identify to A. nidulans PacC and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 21 publications
6
82
1
3
Order By: Relevance
“…In S. cerevisiae, the alkaline-induced transporter Arn4p imports a bacterial siderophore-iron complex (57), thus capitalizing on a bacterial iron acquisition mechanism. In A. nidulans and P. chrysogenum, penicillin synthesis is stimulated at alkaline pH (20,21). ARN4 and the penicillin biosynthesis genes depend upon Rim101p or PacC for expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In S. cerevisiae, the alkaline-induced transporter Arn4p imports a bacterial siderophore-iron complex (57), thus capitalizing on a bacterial iron acquisition mechanism. In A. nidulans and P. chrysogenum, penicillin synthesis is stimulated at alkaline pH (20,21). ARN4 and the penicillin biosynthesis genes depend upon Rim101p or PacC for expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alkaline pH induces transcription of IPNA and other penicillin biosynthetic genes in Aspergillus nidulans and Penicillium chrysogenum (20,21), the protease gene XPR2 in Yarrowia lipolytica (22), and cell wall protein genes in Candida albicans (23)(24)(25). These responses depend upon a conserved signal transduction pathway (20, 22, 26 -29) that is best understood from work on the A. nidulans transcription factor PacC.…”
mentioning
confidence: 99%
“…The positive action of PacCmediated pH regulation overrides the negative effects of a repressing carbon source, although pH and carbon regulation normally act in concert, since poor derepressing carbon sources lead to external alkalinization, possibly because they favor the utilization of the carbon skeleton of amino acids with subsequent release of ammonia (42). These findings stimulated the characterization of pacC in the industrially important producer P. chrysogenum (119), whose product also recognizes in vitro the GCCARG PacC consensus (43,122) in the bidirectional promoter of the acvA-ipnA P. chrysogenum homologues pcbAB-pcbC (119). It has been demonstrated that P. chrysogenum pacC mutations equivalent to alkalinity-mimicking pacC c mutations indeed result in penicillin overproduction (T. Suá-rez, H. N. Arst, Jr., G. Turner, and M. A. Peñalva, international patent application PCT/ES00/00464).…”
Section: Antibiotic Productionmentioning
confidence: 99%
“…An eye-catching feature is the presence of three perfect copies and one imperfect copy of a 6-residue direct repeat in which the perfect copies contain only acidic and glutamine residues (122). Its significance is unclear but is not likely to be great, since it is not present in isofunctional homologues from organisms as closely related as Aspergillus niger and Penicillium chrysogenum (76,119).…”
Section: Pacc Transcription Factormentioning
confidence: 99%
“…At elevated pHs, PacC activates expression of the isopenicillin N synthase gene, which is involved in penicillin biosynthesis. In Penicillium chrysogenum, PacC also activates the expression of the isopenicillin N synthase homologue, pcbC (114). In addition, PacC regulates morphogenesis.…”
Section: Paccmentioning
confidence: 99%